2016
DOI: 10.1007/s00429-016-1345-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of space travel: energetic solar particles cause cell type-specific plasticity of neurotransmission

Abstract: In the not too distant future, humankind will embark on one of its greatest adventures, the travel to distant planets. However, deep space travel is associated with an inevitable exposure to radiation fields. Space-relevant doses of protons elicit persistent disruptions in cognition and neuronal structure. However, whether space-relevant irradiation alters neurotransmission is unknown. Within the hippocampus, a brain region crucial for cognition, perisomatic inhibitory control of pyramidal cells (PCs) is suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 62 publications
4
36
1
8
Order By: Relevance
“…Strikingly, both Tppp and GAD65 were upregulated at the mRNA level in vitro, and at the protein level in vivo, 2 weeks after discontinuation of lithium (PND 91), further confirming the positive modulatory effects of lithium on the neurogenic process as well as the importance of discontinuing the proliferative drive of lithium to allow integration of the newborn cells. The decrease in GAD65 expression after irradiation is in accordance with previous observations demonstrating that irradiation decreases the number and activation of GABAergic, parvalbuminpositive cells in the infralimbic cortex [71], while others reported increased GABA release in cannabinoid1 interneurons, decreased tonic GABAergic signaling, and increased principal cell activation in the hippocampus [72]. Both types of interneurons modulate principal cells activation and we previously demonstrated that early life irradiation increases excitability and impairs long-term potentiation in the adult dentate gyrus [73].…”
Section: Identification Of Mechanismssupporting
confidence: 92%
“…Strikingly, both Tppp and GAD65 were upregulated at the mRNA level in vitro, and at the protein level in vivo, 2 weeks after discontinuation of lithium (PND 91), further confirming the positive modulatory effects of lithium on the neurogenic process as well as the importance of discontinuing the proliferative drive of lithium to allow integration of the newborn cells. The decrease in GAD65 expression after irradiation is in accordance with previous observations demonstrating that irradiation decreases the number and activation of GABAergic, parvalbuminpositive cells in the infralimbic cortex [71], while others reported increased GABA release in cannabinoid1 interneurons, decreased tonic GABAergic signaling, and increased principal cell activation in the hippocampus [72]. Both types of interneurons modulate principal cells activation and we previously demonstrated that early life irradiation increases excitability and impairs long-term potentiation in the adult dentate gyrus [73].…”
Section: Identification Of Mechanismssupporting
confidence: 92%
“…It is unknown how the HZE particle parameters used here influence dentate gyrus GABAergic interneurons and mossy cells in mature mice. However, exposure to other energetic particles that comprise space radiation alters the inhibitory network in the dentate gyrus and other hippocampal subregions of young adult rodents 86,87 . In the future, evaluation of GABAergic signaling and other measures relevant to sparse encoding (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to other energetic particles that comprise space radiation alters the inhibitory network in the dentate gyrus and other hippocampal subregions of young adult rodents (131,132) . In A third possibility -and related to conditions that favor sparse encoding -is that HZE particle exposure increases dentate gyrus neurogenesis.…”
Section: Discussionmentioning
confidence: 99%